(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Curriculum and Assessment Policy Statement for History (2011) encourages an active and critical approach to learning. This principle requires History teachers to structure learning environments that will enable active learner participation and meaningful learning. This article reports on a quantitative research study conducted in schools in the Free State Province to establish the extent to which History learners are exposed to the different characteristics of a powerful learning environment (PLE) as espoused by both De Corte and Masui (2004) and Donovan and Bransford (2005). Findings revealed that History learners are exposed to the different aspects of PLEs, albeit at different levels.